Cerebral death in the newborn and in the newborn with anencephaly - Di Rocco, Concezio (Medicina e Morale, 1993)
Starting with the confirmation, in the 1950's, of the inadequacy of the traditional criteria in determining clinical death (ceasing of respiratory and heart activities), the article describes the work carried out and widely accepted, despite continuous refinements, by the "ad hoc" Committee created in the 1960's by the Harvard Faculty of Medicine with regard to precise criteria for determining cerebral death. Nevertheless no indication was given for death in the pediatric age. In order to do this specific guidelines were formulated, for example, by the "Children's Hospital" of Boston and by the "Task Force" to determine cerebral death in children (USA). The author concludes the article with a discussion on the problem of the newborn as a source of transplanting organs, with particular reference to the anencephalic newborn.